Comparing simulated PSC optical properties with CALIPSO observations during the 2010 Antarctic winter. Issue 2 (28th January 2017) - Zhu, Yunqian; Toon, Owen B.; Pitts, Michael C.; Lambert, Alyn; Bardeen, Charles; Kinnison, Douglas E.
Abstract: We simulate polar stratospheric clouds (PSCs) during the Antarctic winter of 2010 using the Specified Dynamics version of the Whole Atmosphere Community Climate Model/Community Aerosol and Radiation Model for Atmospheres (SD‐WACCM/CARMA) model. The current PSC model contains microphysical schemes for supercooled ternary solutions (STS) and nitric acid trihydrate (NAT) particles, as well as a prognostic treatment for PSC ice particles and dehydration. Our simulations and CALIPSO satellite data suggest two major NAT particle formation mechanisms. The first mechanism is the nucleation of NAT from STS. Our model, with homogeneous nucleation rates of NAT from STS constrained by observations from the Arctic winter of 2010–2011, reproduces optical properties observed by CALIPSO over Antarctica in May and the timing of denitrification observed by the Microwave Limb Sounder within their uncertainties. On the other hand, the CALIPSO data indicate that our simulations are missing clouds containing small NAT particles with large number densities. We suggest these particles are most likely to form from ice clouds or STS in gravity waves, as found by previous investigations. The simulated cloud coverage agrees with the CALIPSO cloud coverage within a few percent on average with a correlation coefficient of 0.83. However, using the CALIPSO classification algorithm, simulated ice clouds often fall into Mix categories under the denitrified and dehydrated conditions. The model needs an improved ice microphysical representation, not only to allow ice particles to be a source of NAT but also to provide information on ice cloud particle number and size so that ice cloud optical properties can be more precisely calculated for comparison with CALIPSO data. Key Points: Three‐dimensional modeling of polar stratospheric clouds simulates denitrification, dehydration, and cloud coverage within error bars of observations CALIPSO PSC algorithm misclassifies ice PSCs into the Mixed composition categories under dehydrated and denitrified conditions Both the simulations and the observations suggest two major NAT formation mechanisms in the Antarctic 2010 winter